La solución pacífica de conflictos en la convivencia escolar de los docentes en la Escuela “Manuel Salcedo” de la ciudad de Latacunga 2015 - Sailema Soria, Jenny del Pilar (2015)
The goal research is to improve labor relations coexistence and communication between teachers at "Manuel Salcedo School". The miscommunication and lack values in the institution have affected the relationship between teachers. This situation affected on project implementation. The methods applied in order to get data were the director interview, teachers’ surveys and institutional administrative staff. Question item by item were analyzed and interpreted in order to carry out the conclusion of the problem. The development and implementation values’ guide allow teachers to build relationships and mutual support. This action will contribute to the future development of this school. It arises promote human values such as educational bodies with academic excellence. Furthermore, this allows achieving a communicative, conventional, unique atmosphere in the teaching of values. Finally, this will be innovative and creative.